1999
DOI: 10.1074/jbc.274.43.30858
|View full text |Cite
|
Sign up to set email alerts
|

The p38 Mitogen-activated Protein Kinase Is Required for NF-κB-dependent Gene Expression

Abstract: Endotoxin-induced cytokine gene transcription in monocytes and macrophages is regulated in part by NF-B. We have previously shown that the p38 mitogenactivated protein (MAP) kinase is necessary for endotoxin-induced cytokine gene transcription. Due to the fact that most cytokine promoter sequences have active NF-B sites, we hypothesized that the p38 MAP kinase was necessary for NF-B-dependent gene expression. We found that NF-B-dependent gene expression was reduced to near control levels with either SB 203580 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
332
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(353 citation statements)
references
References 46 publications
19
332
2
Order By: Relevance
“…65 Studies have shown that ERK1/2 and p38 are involved in the transcriptional activation of NF-B. 66,67 In the present study, we further investigated the effect of PFE on the pattern of NF-B activation and its nuclear translocation by TPA in CD-1 mouse skin. NF-B has emerged as one of the most promising molecular targets in the prevention of cancer.…”
Section: Discussionmentioning
confidence: 88%
“…65 Studies have shown that ERK1/2 and p38 are involved in the transcriptional activation of NF-B. 66,67 In the present study, we further investigated the effect of PFE on the pattern of NF-B activation and its nuclear translocation by TPA in CD-1 mouse skin. NF-B has emerged as one of the most promising molecular targets in the prevention of cancer.…”
Section: Discussionmentioning
confidence: 88%
“…Accordingly, previous studies demonstrated that JNK 1/2 (Zhou et al, 2008) and p38 MAPK, but not ERK 1/2 (Chen and Wang, 1999), modulated iNOS expression and NO production in LPSstimulated Raw 264.7 macrophages. In addition, activated MAPKs and PI3K/Akt were also implicated in NF-κB activation (Carter et al, 1999;Nakano et al, 1998), being NF-κB one of the critical transcription factors that controls iNOS gene expression in macrophages (Geller and Billiar, 1998). Cy extract also inhibited p38 MAPK, JNK 1/2 and NF-κB signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the iNOS expression could also be modulated by phosphatidylinositol-3-kinase (PI3K)/Akt pathway (Salh et al, 1998), a serine/threonine kinase activated in response to certain growth factors and cytokines that provides a strong cell survival signal (Crawley et al, 1996;Gold et al, 1994). MAPKs and Akt also play A c c e p t e d M a n u s c r i p t 5 a critical role in the activation of nuclear factor (NF)-κB (Carter et al, 1999;Nakano et al, 1998). The NF-κB transcription factor regulates the expression of many genes involved in immune and inflammatory responses, including iNOS and COX-2 (Geller and Billiar, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…p38 MAPK has been implicated in the activation of NF-κB (Carter et al, 1999). Other investigators have demonstrated that p38 MAPK-specific inhibitor SB203580 markedly attenuated NF-κB-dependent transcription (Conejo et al, 2001;Thirunavukkarasu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Both p38 MAPK and NF-κB are crucial to the signaling pathway that leads to the proinflammatory cytokine production (Baldwin, 1996;Raingeaud et al, 1995). P38 MAPK is a key mediator in organ dysfunction relating to inflammatory states, and acts as an important regulator of cell proliferation, differentiation, and production of proinflammatory cytokines (Carter et al, 1999;Thobe et al, 2006). NF-κB plays a key role in the transcriptional regulation of adhesion molecules, chemokines and cytokines involved in acute inflammatory responses (Baldwin, 1996).…”
Section: Discussionmentioning
confidence: 99%